Lilac girls: a novel (Lilac Girls, ,, 2016)
Manhattan, 1939. New York socialite Caroline Ferriday's biggest problem is resisting the advances of a married actor. Across the Atlantic Kasia Kuzmerick, a Polish Catholic teenager, is affected when Germany declares war on Poland. As tensions rise Caroline's interest in aiding the war effort in France grows; she hears about the dire situation at the Ravensbrück all-female concentration camp. Kasia's carefree youth is replaced by a fervor for the Polish resistance movement. Through Ravensbrück-- and the horrific atrocities taking place there told in part by an infamous German surgeon, Herta Oberheuser-- the two women's lives converge in unprecedented ways.

We were the lucky ones (Center Point Large Print edition historical fiction, ,, 2017)
It is the spring of 1939, and three generations of the Kurc family are doing their best to live normal lives, even as the shadow of war grows ever closer. The talk around the family Seder table is of new babies and budding romance, not of the increasing hardships facing Jews in their hometown of Radom, Poland. As the horrors overtaking Europe become inescapable, the Kurc family will be flung to the far corners of the earth, each desperately trying to chart his or her own path toward safety. Driven by an extraordinary will to survive, the Kurcs must rely on hope, ingenuity, and inner strength to persevere. (Based on the author's own family.)

Salt to the sea: a novel (Thorndike Press large print literacy bridge, ,, 2016)
World War II is drawing to a close in East Prussia, and thousands of refugees are on a desperate trek toward freedom. When their paths converge in route to the ship that promises salvation, Joana, Emilia, and Florian find their strength, courage, and trust in one another tested with each step closer toward safety. When tragedy strikes the Wilhelm Gustloff, they must fight for the same thing: survival.

All the light we cannot see: a novel (Thorndike Press large print reviewers' choice, ,, 2014)
"From the highly acclaimed, multiple award-winning Anthony Doerr, a stunningly ambitious and beautiful novel about a blind French girl and a German boy whose paths collide in occupied France as both try to survive the devastation of World War II. Marie Laure lives with her father in Paris within walking distance of the Museum of Natural History where he works as the master of the locks (there are thousands of locks in the museum). When she is six, she goes blind, and her father builds her a model of their neighborhood, every house, every manhole, so she can memorize it with her fingers and navigate the real streets with her feet and cane. When the Germans occupy Paris, father and daughter flee to Saint-Malo on the Brittany coast, where Marie-Laure's agoraphobic great uncle lives in a tall, narrow house by the sea wall. In another world in Germany, an orphan boy, Werner, grows up with his younger sister, Jutta, both enchanted by a crude radio Werner finds. He becomes a master at building and fixing radios, a talent that wins him a place at an elite and brutal military academy and, ultimately, makes him a highly specialized tracker of the Resistance. Werner travels through the heart of Hitler Youth to the far-flung outskirts of Russia, and finally into Saint-Malo, where his path converges with Marie-Laure. Doerr's gorgeous combination of soaring imagination with observation is electric. Deftly interweaving the lives of Marie-Laure and Werner, Doerr illuminates the ways, against all odds, people try to be good to one another. Ten years in the writing, All the Light We Cannot See is his most ambitious and dazzling work"--

Number the stars (Houghton Mifflin, Playaway Digital Audio, HarperCollins, Random House/Listening Library, Books on Tape, 2007)
In 1943, during the German occupation of Denmark, ten-year-old Annemarie learns how to be brave and courageous when she helps shelter her Jewish friend from the Nazis.

The splendid and the vile: a saga of Churchill, family, and defiance during the blitz (Crown, Penguin Random House, Books on Tape, 2020)
The #1 New York Times bestselling author of The Devil in the White City and Dead Wake delivers a fresh and compelling portrait of Winston Churchill and London during the Blitz On Winston Churchill's first day as prime minister, Hitler invaded Holland and Belgium. Poland and Czechoslovakia had already fallen, and the Dunkirk evacuation was just two weeks away. For the next twelve months, Hitler would wage a relentless bombing campaign, killing 45,000 Britons. It was up to Churchill to hold the country together and persuade President Franklin Roosevelt that Britain was a worthy ally-and willing to fight to the end. In The Splendid and the Vile, Erik Larson shows, in cinematic detail, how Churchill taught the British people "the art of being fearless." It is a story of political brinkmanship, but it's also an intimate domestic drama set against the backdrop of Churchill's prime-ministerial country home, Chequers; his wartime retreat, Ditchley, where he and his entourage go when the moon is brightest and the bombing threat is highest; and of course 10 Downing Street in London. Drawing on diaries, original archival documents, and once-secret intelligence reports-some released only recently-Larson provides a new lens on London's darkest year through the day-to-day experience of Churchill and his family: his wife, Clementine; their youngest daughter, Mary, who chafes against her parents' wartime protectiveness; their son, Randolph, and his beautiful, unhappy wife, Pamela; Pamela's illicit lover, a dashing American emissary; and the cadre of close advisers who comprised Churchill's "Secret Circle," including his lovestruck private secretary, John Colville; newspaper baron Lord Beaverbrook; and the Rasputin-like Frederick Lindemann. The Splendid and the Vile takes readers out of today's political dysfunction and back to a time of true leadership, when-in the face of unrelenting horror-Churchill's eloquence, courage, and perseverance bound a country, and a family, together.
Bleak Expectations , The Rising Threat , A Certain Eventuality , Dread , Blood and Dust , The Americans , Love Amid the Flames , One Year to the Day , Epilogue.

The hiding place (Chosen books, a division of Baker Publishing Group, Blackstone Audiobooks, christianaudio.com, Blackstone Audio Books, Blackstone Publishing, Chosen Books, Baker Publishing Group, 2009)
The amazing story of Corrie ten Boom, a heroine of the Dutch Resistance who helped Jews escape from the Nazis and became one of the most remarkable evangelists of the 20th century, is told in her classic memoir, now repackaged for a new generation.
The one hundredth birthday party , Full table , Karel , The watch shop , Invasion , The secret room , Eusie , Storm clouds gather , The raid , Scheveningen , The lieutenant , Vught , Ravensbruck , The blue sweater , The three visions.

Poland 1939: the outbreak of World War II (Basic Books, 2020)
"For Americans, World War II began in December of 1941, with the bombing of Pearl Harbor; in Soviet historical accounts, the war was prompted by the German invasion of June 1941; for the British and the French, the war was not taken seriously until the German forces penetrated French territory in May 1940. But for Poland, the war began on September 1, 1939 when the Nazi army invaded Poland by land and by air, where they were soon joined by Stalin's army. In Poland 1939, Roger Moorhouse introduces the September Campaign as the triggering event of World War II and challenges the prevailing historical understanding of the start the war. The Polish campaign of 1939 is the least written-about and least understood campaign of World War II. Although many of the doctrines and practices that would feature so strongly throughout the war - the targeting of civilians, race war, Blitzkrieg, aerial bombing - would see their debut in Poland, the campaign is rarely given any real scrutiny. In his close examination of the often-overlooked September Campaign, Moorhouse explores the Anglo-French betrayal of Poland, when both Britain and France pledged to defend Poland but then did nothing of the sort (their inaction resulted in the slaughter of 16,000 Polish civilians). In Poland 1939, Moorhouse offers an insightful account of the September Campaign, and unravels the misconceptions and myths that have clouded the beginnings of World War II. This is the first English-language history of the September Campaign. Moorhouse draws from memoirs of generals, diplomats, letters of soldiers and civilian diaries, as well as private and previously untapped documentary archives in Poland, to expose the true history of the September Campaign, the event that set the tone for the bloody conflict to come."--

The book of lost names: a novel (Simon & Schuster Audio, Gallery Books, Center Point Large Print, 2020)
Eva Traube Abrams, a semi-retired librarian in Florida, is shelving books one morning when her eyes lock on a photograph in a magazine lying open nearby. She freezes; it's an image of a book she hasn't seen in sixty-five years--a book she recognizes as The Book of Lost Names. The accompanying article discusses the looting of libraries by the Nazis across Europe during World War II--an experience Eva remembers well--and the search to reunite people with the texts taken from them so long ago. The book in the photograph, an eighteenth-century religious text thought to have been taken from France in the waning days of the war, is one of the most fascinating cases. Now housed in Berlin's Zentral- und Landesbibliothek library, it appears to contain some sort of code, but researchers don't know where it came from--or what the code means. Only Eva holds the answer--but will she have the strength to revisit old memories and help reunite those lost during the war? As a graduate student in 1942, Eva was forced to flee Paris after the arrest of her father, a Polish Jew. Finding refuge in a small mountain town in the Free Zone, she begins forging identity documents for Jewish children fleeing to neutral Switzerland. But erasing people comes with a price, and along with a mysterious, handsome forger named Rémy, Eva decides she must find a way to preserve the real names of the children who are too young to remember who they really are. The records they keep in The Book of Lost Names will become even more vital when the resistance cell they work for is betrayed and Rémy disappears.

Unbroken: a World War II airman's story of survival, resilience, and redemption (Random House Publishing Group, Random House, Books on Tape, 2010)
#1 NEW YORK TIMES BESTSELLER • The incredible true story of survival and salvation that is the basis for two major motion pictures: Unbroken and Unbroken: Path to Redemption. “Extraordinarily moving . . . a powerfully drawn survival epic.”—The Wall Street Journal Hailed as the top nonfiction book of the year by Time magazine • Winner of the Los Angeles Times Book Prize for biography On a May afternoon in 1943, an Army Air Forces bomber crashed into the Pacific Ocean and disappeared, leaving only a spray of debris and a slick of oil, gasoline, and blood. Then, on the ocean surface, a face appeared. It was that of a young lieutenant, the plane’s bombardier, who was struggling to a life raft and pulling himself aboard. So began one of the most extraordinary odysseys of the Second World War. The lieutenant’s name was Louis Zamperini. In boyhood, he’d been a cunning and incorrigible delinquent, breaking into houses, brawling, and fleeing his home to ride the rails. As a teenager, he had channeled his defiance into running, discovering a prodigious talent that had carried him to the Berlin Olympics and within sight of the four-minute mile. But when war had come, the athlete had become an airman, embarking on a journey that led to his doomed flight, a tiny raft, and a drift into the unknown. Ahead of Zamperini lay thousands of miles of open ocean, leaping sharks, a foundering raft, thirst and starvation, enemy aircraft, and, beyond, a trial even greater. Driven to the limits of endurance, Zamperini would answer desperation with ingenuity; suffering with hope, resolve, and humor; brutality with rebellion. His fate, whether triumph or tragedy, would be suspended on the fraying wire of his will. Laura Hillenbrand writes with the same rich and vivid narrative voice she displayed in Seabiscuit. Telling an unforgettable story of a man’s journey into extremity, Unbroken is a testament to the resilience of the human mind, body, and spirit.

Catch-22 (Simon & Schuster Audio, HarperCollins, Simon & Schuster/Scribner Paperback Fiction, Books on Tape, Simon & Schuster, 1996)
Set in the closing months of World War II in an American bomber squadron off the coast of Italy, Catch-22 is the story of a bombardier named Yossarian who is frantic and furious because thousands of people he has never even met keep trying to kill him.

The things we cannot say (Graydon House, Harlequin Audio, Graydon House Books, 2019)
In 1942, Europe remains in the relentless grip of war. Just beyond the tents of the Russian refugee camp she calls home, a young woman speaks her wedding vows. It's a decision that will alter her destiny ... and it's a lie that will remain buried until the next century. Since she was nine years old, Alina Dziak knew she would marry her best friend, Tomasz. Now fifteen and engaged, Alina is unconcerned by reports of Nazi soldiers at the Polish border, believing her neighbors that they pose no real threat, and dreams instead of the day Tomasz returns from college in Warsaw so they can be married. But little by little, injustice by brutal injustice, the Nazi occupation takes hold, and Alina's tiny rural village, its families, are divided by fear and hate. Then, as the fabric of their lives is slowly picked apart, Tomasz disappears. Where Alina used to measure time between visits from her beloved, now she measures the spaces between hope and despair, waiting for word from Tomasz and avoiding the attentions of the soldiers who patrol her parents' farm. But for now, even deafening silence is preferable to grief. Slipping between Nazi-occupied Poland and the frenetic pace of modern life, Kelly Rimmer creates an emotional and finely wrought narrative. The Things We Cannot Say is an unshakable reminder of the devastation when truth is silenced ... and how it can take a lifetime to find our voice before we learn to trust it.

The lost girls of Paris (Harper Audio, Inc, Harlequin Audio, Park Row Books, 2019)
"A ... story of friendship and courage centered around three women and a ring of female secret agents during World War II"--

Engineers of victory: the problem solvers who turned the tide in the Second World War (Random House Publishing Group, Random House, 2013)
Analyzes previously unexplored strategic factors that contributed to the Allied victory in World War II, sharing assessments of ambitious goals successfully pursued by FDR, Churchill, and other attendees at the Casablanca Conference.
How to get convoys safely across the Atlantic , How to win command of the air , How to stop the Nazi blitzkrieg , How to advance on an enemy-held shore , How to defeat the Pacific Ocean's "tyranny of distance".

Hell to pay: Operation Downfall and the invasion of Japan, 1945-47 (Naval Institute Press, 2017)
Description Not Provided
Foreword to the first edition: "Three colonels" / by Stanley Weintraub --, The maximum "bloodletting and delay" --, Spinning the casualties --, The First Army and Kwantung redeployments --, The Pacific buildup and Berlin decision --, "Not the recipe for victory" --, The decision --, Japanese defense plans --, "Victory might be salvaged" --, The "manpower box" --, Mistakes and misperceptions --, "To break Japan's spine" --, What is defeat? --, The amphibious operation --, On the ground --, Unexamined factors --, A "target-rich environment: --, The Hokkaido myth --, Half a million Purple Hearts --, "Punishment from heaven" --, Epilogue: Extract from a letter written by James Michener, October 20, 1995 --, Appendix A. G-2 estimates of enemy situation on Kyushu, U.S. Sixth Army, August 1, 1945 --, Appendix B. G-2 analysis of Japanese plans for the defense of Kyushu, U.S. Sixth Army, December 31, 1945 --, Appendix C. Proclamation defining terms for Japanese surrender issued at Potsdam, July 26, 1945 (Potsdam Declaration) --, Appendix D. Operation Blacklist, the occupation of Japan.

Operation Mincemeat: how a dead man and a bizarre plan fooled the Nazis and assured an Allied victory (Crown, Center Point Publishing, Harmony, Books on Tape, 2010)
From the acclaimed author of "Agent Zigzag" comes an extraordinary account of the most successful deception--and certainly the strangest--ever carried out in World War II, one that changed the prospects for an Allied victory. The purpose of the plan--code named Operation Mincemeat--was to deceive the Nazis into thinking that Allied forces were planning to attack southern Europe by way of Greece or Sardinia, rather than Sicily, as the Nazis had assumed, and the Allies ultimately chose.

Killing the rising sun: how America vanquished World War II Japan (Bill O'Reilly's Killing, ,, 2016)
Autumn 1944. World War II is nearly over in Europe but is escalating in the Pacific, where American soldiers face an opponent who will go to any length to avoid defeat. The Japanese army follows the samurai code of Bushido, stipulating that surrender is a form of dishonor. This book takes readers to the bloody tropical-island battlefields of Peleliu and Iwo Jima and to the embattled Philippines, where General Douglas MacArthur has made a triumphant return and is plotting a full-scale invasion of Japan. Across the globe in Los Alamos, New Mexico, Dr. J. Robert Oppenheimer and his team of scientists are preparing to test the deadliest weapon known to mankind. In Washington, DC, Harry Truman ascends to the presidency after FDR dies in office, only to face the most important political decision in history: whether to use that weapon. And in Tokyo, Emperor Hirohito, who is considered a deity by his subjects, refuses to surrender, despite a massive and mounting death toll.

The war that saved my life (Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, Findaway World, LLC, Books on Tape, Penguin Young Readers Group, 2015)
A young disabled girl and her brother are evacuated from London to the English countryside during World War II, where they find life to be much sweeter away from their abusive mother.

Beyond that, the sea (Celadon Books, Macmillan Audio, 2023)
"A sweeping, tenderhearted love story, Beyond That, the Sea by Laura Spence-Ash tells the story of two families living through World War II on opposite sides of the Atlantic Ocean, and the shy, irresistible young woman who will call them both her own. As German bombs fall over London in 1940, working-class parents Millie and Reginald Thompson make an impossible choice: they decide to send their eleven-year-old daughter, Beatrix, to America. There, she'll live with another family for the duration of the war, where they hope she'll stay safe. Scared and angry, feeling lonely and displaced, Bea arrives in Boston to meet the Gregorys. Mr. and Mrs. G, and their sons William and Gerald, fold Bea seamlessly into their world. She becomes part of this lively family, learning their ways and their stories, adjusting to their affluent lifestyle. Bea grows close to both boys, one older and one younger, and fills in the gap between them. Before long, before she even realizes it, life with the Gregorys feels more natural to her than the quiet, spare life with her own parents back in England. As Bea comes into herself and relaxes into her new life-summers on the coast in Maine, new friends clamoring to hear about life across the sea-the girl she had been begins to fade away, until, abruptly, she is called home to London when the war ends. Desperate as she is not to leave this life behind, Bea dutifully retraces her trip across the Atlantic back to her new, old world. As she returns to post-war London, the memory of her American family stays with her, never fully letting her go, and always pulling on her heart as she tries to move on and pursue love and a life of her own. As we follow Bea over time, navigating between her two worlds, Beyond That, the Sea emerges as a beautifully written, absorbing novel, full of grace and heartache, forgiveness and understanding, loss and love"--

The guardian: a novel (Guardian, 1,, 2013)
Thirteen-year-old Carruthers "Danni" McAllister receives an enchanted pouch as a birthday gift from her grandfather, which she must use to save her family from the deadly extortionist known as "El Cobra," who is holding her family for a $20 million ransom.